Unexpected complications with head and neck hydrogel microsphere particle embolization: A case series and a technical note. Issue 1 (February 2017) - Khoury, Naim N; Champagne, Pierre-Olivier; Kotowski, Marc; Raymond, Jean; Roy, Daniel; Weill, Alain
Endovascular particle embolization is a common procedure with a relatively safe profile. We report here four cases in which cranial nerves, skin and mucosal ischemic complications occurred with the use of hydrogel microspheres (250–500 µm in size). Given the compressibility and higher penetration potential of microsphere particles compared with polyvinyl alcohol particles of similar size, we suggest oversizing hydrogel microsphere particles for head and neck embolizations.